Fred B. Craddock, The Collected Sermons of Fred B. Craddock, and Fred B. Craddock, Dale Goldsmith and Joy V. Goldsmith, Speaking of Dying: Recovering the Church’s Voice in the Face of Death (Homiletic, 2016)
N/A